Increasing distillable key rate from bound entangled states by using local filtration - Mishra, Mayank; Arvind (American Physical Society, 2020)
We show the enhancement of a distillable key rate for quantum key distribution (QKD) by local filtering for several bound entangled states. Through our paper, it becomes evident that the local filtration operations, whereas transforming one bound entangled state to another, have the potential to increase the utility of the new state for QKD. We demonstrate three examples of “one-way distillable key rate” enhancement by local filtering and, in this process, discover new bound entangled states which are key distillable
Only IISERM authors are available in the record.
Keywords: Quantum key distribution (QKD); Local filtering